Direct health implications of e-cigarette use: a systematic scoping review with evidence assessment - Izquierdo-Condoy, Juan S.; Naranjo-Lara, Patricio; Morales-Lapo, Estefanía; Hidalgo, Marlon R.; Tello-De-la-Torre, Andrea; Vásconez-Gonzáles, Eduardo; Salazar-Santoliva, Camila; Loaiza-Guevara, Valentina; Rincón Hernández, Wendy; Becerra, Diego Alexander; González, María Belén Delgado; López-Cortés, Andrés; et al. (Frontiers in Public Health, 2024)
Background E-cigarettes are often marketed as a less harmful alternative to traditional tobacco cigarettes. Despite their popularity, the evidence regarding their effects on human health remains unclear and is filled with complexities. Objectives This systematic review aims to elucidate the direct effects of electronic cigarette use on human health, carefully distinguishing between the specific characteristics of the populations studied. Methodology Adhering to the PRISMA guidelines, we conducted a comprehensive search in PubMed/Medline, Web of Science, Scopus, and Google Scholar databases without date restrictions, including articles in both Spanish and English. This approach enabled the identification and analysis of primary studies to understand the direct effect of electronic cigarettes on human health. Results A total of 33 studies were included that evaluated cardiovascular, pulmonary, renal, weight and fertility effects. Only five studies analyzed e-cigarettes in healthy populations and seven studies compared healthy individuals against smokers. The effects evaluated on smokers or former tobacco smokers were apparently positive, however, among healthy individuals, increased heart rate, mean arterial pressure, oxidative stress, alteration of respiratory epithelial cells and increased airflow resistance were found. Conclusion Smokers or former smokers who switch to e-cigarettes may reduce their exposure to carcinogens and lower their risk of developing severe health issues associated with conventional smoking. However, in healthy individuals who have never smoked traditional cigarettes, the use of e-cigarettes introduces several cardiovascular and respiratory adverse effects. These findings suggest that while e-cigarettes can be a strategic harm reduction tool for smokers, they are not a safe option for non-smokers.